33 Clinical senate fellowships as a forum for developing future clinical and medical leaders. (3rd November 2019) - Hall, Rebecca; Miller, Christopher J; Popoola, Remi; Gavens, Lucy; Malaga, Elizabeth Gonzalez; Issa, Eyad; Orrock, Emma; Evans, Alyson; Harrison, Lara; Dennison, Ashley; Rashid, Aly
Abstract : Aims: The East Midlands Clinical Senate is one of twelve regional clinical senates. Clinical senates act as a forum of multi-professional clinical leaders who can offer independent and objective clinical advice to support commissioners and other stakeholders to make the best decisions about health care for their local populations. The East Midlands Clinical Senate recognised this would provide a unique opportunity to recruit clinical research fellows, creating the opportunity to support leadership development and enhance our ability to produce high quality research to support evidence-based decision making among health and social care leaders. Methods: A competitive recruitment process engaged six clinical fellows from a variety of specialties, for one session a week over a 12 month period. The clinical fellows were given the opportunity to work with senior leaders to develop their skills in leadership, strategy, project management and health policy. The fellows were exposed to the full spectrum of clinical senate work, clinical reviews, proactive projects, production and presentation of reports, as well as opportunities to attend meetings with senior leaders both locally and nationally. Conclusion s: The clinical fellows enhanced the senate work programme by undertaking proactive projects. This allowed collaborative working with partner organisations, to evaluate models of care following service reorganisation, review the evidence regarding systems organisation and collaborative working for winter pressures and generate a narrative to bring physical activity as a treatment to the local healthcare agenda. Clinical fellowships offering the level of exposure to the rich opportunities for clinical leadership development that the East Midlands Clinical Senate has been able to offer are rare. Clinical senates provide innovative arenas for fellows to experience systems based thinking with tangible involvement as leadership figures and supporting leadership career development.